2000
DOI: 10.1074/jbc.m001087200
|View full text |Cite
|
Sign up to set email alerts
|

A Role of the Ca2+/Mg2+-dependent Endonuclease in Apoptosis and Its Inhibition by Poly(ADP-ribose) Polymerase

Abstract: Apoptosis is characterized by various cell morphological and biochemical features, one of which is the internucleosomal degradation of genomic DNA. The role of the human chromatin-bound Ca 2؉ -and Mg 2؉ -dependent endonuclease (CME) DNAS1L3 and its inhibition by poly(ADP-ribosyl)ation in the DNA degradation that accompanies apoptosis was investigated. The nuclear localization of this endonuclease is the unique feature that distinguishes it from other suggested apoptotic nucleases. Purified recombinant DNAS1L3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 57 publications
(79 reference statements)
2
76
0
1
Order By: Relevance
“…31 It has been reported that, at early stages of apoptosis, DNaseY can be inactivated by PARP-1 through the poly-ADPribosylation mechanism. 18,19 Here we found a significant upregulation of PARP-1 in the DNaseY-overexpressing cells (Figure 11a). Therefore, it is possible that PARP-1 acts both as a sensor to detect ssb and at the same time to synthesize negatively charged ADP-ribose polymers to inhibit the endonuclease that creates them.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…31 It has been reported that, at early stages of apoptosis, DNaseY can be inactivated by PARP-1 through the poly-ADPribosylation mechanism. 18,19 Here we found a significant upregulation of PARP-1 in the DNaseY-overexpressing cells (Figure 11a). Therefore, it is possible that PARP-1 acts both as a sensor to detect ssb and at the same time to synthesize negatively charged ADP-ribose polymers to inhibit the endonuclease that creates them.…”
Section: Discussionmentioning
confidence: 65%
“…This is in agreement with the previous studies, which reported that transfection of the same nuclease into HeLa cells or mouse skin fibroblasts increased cell death only in response to apoptotic stimuli, but not by itself. 9,18 In our cell system, overexpression of DNaseY led to the activation of DNA repair pathways. The components of both repair systems, the Polb-XRCC1-Lig3 pathway, which conducts both short and long-patch repair as well as the Pold/e-PCNALig1 pathway, which provides an alternative or 'backup' mechanism for ssb repair and often conducts long-patch break repair, 24 were clearly upregulated in the DNaseYoverexpressing cells (Figure 11e and f).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The digestion by exogenous DNase I of fixed nuclei derived from viable cells yields a fairly similar initial appearance of the chromatin degradation (45). In the later phases of DNA digestion in apoptotic cells, several endogenous nucleases and auxiliary proteins cooperate to generate an oligonucleosome ladder, a hallmark of apoptosis (19,(46)(47)(48)(49)(50)(51)(52)(53). The nuclei of apoptotic cells are degraded before lysis of the cytoplasmic membrane.…”
Section: Discussionmentioning
confidence: 99%